Translation Techniques Used in Biological Terms in Bilingual Biology 1 Textbook for Senior High School Class X - Nurhidayah, Vibry Andina; Khoshimov, Maksud (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2024)
This article investigates the translation of English biological terms into Indonesian in a high school textbook. Using a descriptive-qualitative approach, it examines translation techniques, drawing on Molina and Albir's framework. Data collection methods include content analysis. The study identifies four translation techniques: pure borrowing, literal, borrowing, and amplification. Pure borrowing is the most common technique used. The discussion emphasizes the importance of balancing linguistic accuracy and cultural relevance. The research contributes to understanding translation strategies in cross-cultural communication, aligning with Molina and Albir's framework. Overall, it sheds light on translators' choices in conveying biological concepts in bilingual education.